An Appraisal of the Forest Potential of Bastar for Industrial Development - Seth, V. K. (Indian Forester, 1972)
The forests of Bastar district in Madhya Pradesh are very much in the news. The rich, untapped resources of the region await stepped-up development. The paper acts out to assess the forest resources of Bastar and to formulate an action programme for an integrated development of these resources, and forest-based industries. The principles on whicb the forests could be worked have also been touched upon briefly. The region holds a promise of yielding hlgb dividends on investments and, apart from providing gainful employment to the rural populace, it can help substantially in meeting the spiralling needs of the country of wood and wood-products.